Local Wisdom of the Mangain Tradition in Batak Toba - Nori Marta Marselina br. Simatupang (Tradition and Modernity of Humanity, 2026)
This study examines the local wisdom embodied in the Mangain tradition of the Batak Toba community and explores its role in preserving cultural identity, kinship, and social harmony amid the challenges of modernization. Mangain is a customary practice of granting a Batak clan (ulos) to an adopted child or an individual from outside the Batak ethnic group, thereby integrating the person into the Batak Toba patrilineal kinship system. The tradition is commonly performed in cases of child adoption and interethnic marriage, where it serves as a legitimate mechanism for establishing social status, inheritance rights, and obligations within the dalihan na tolu kinship structure. Employing a qualitative descriptive approach with an anthropolinguistic perspective, this study analyzes the linguistic expressions, ritual performances, symbolic objects, and cultural meanings embedded in each stage of the Mangain ceremony. The findings reveal that the tradition embodies fundamental values of local wisdom, including respect for elders and ancestors, kinship solidarity, mutual responsibility, social justice, cultural identity, and communal cooperation. These values are transmitted through ritual speeches, the presentation of ulos, ceremonial food, blessings, and symbolic exchanges that reinforce collective memory and cultural continuity across generations. Furthermore, the study highlights that Mangain functions not only as a legal-customary process but also as a cultural mechanism for integrating outsiders into the Batak social system while maintaining harmony among families. Nevertheless, globalization, migration, and changing lifestyles have contributed to the simplification of ritual practices and a gradual decline in understanding the philosophical significance of Mangain, particularly among younger generations. Therefore, preserving the Mangain tradition is essential for safeguarding Batak Toba local wisdom, strengthening cultural resilience, and ensuring the continuity of indigenous knowledge and identity in contemporary society.